The profile of Porphyromonas gingivalis kgp biotype and fimA genotype mosaic in subgingival plaque samples. Issue 2 (1st December 2014) - Nadkarni, Mangala A.; Chhour, Kim-Ly; Chapple, Cheryl C.; Nguyen, Ky-Anh; Hunter, Neil
Abstract: Combined analysis of allelic variation of the virulence-associated, strain-specific lys-gingipain gene ( kgp ) and major fimbrial gene ( fimA ) of Porphyromonas gingivalis was undertaken in 116 subgingival plaque samples to understand the kgp biotype and fimA genotype profile in a subject-specific manner. Allelic variation in the polyadhesin domain of kgp from P. gingivalis strains 381 (ATCC 33277), HG66 and W83 generated four isoforms corresponding to four biotypes of P. gingivalis . Similarly, variation in the fimA subunit of the fimA gene cluster of P. gingivalis resulted in six fimA genotypes. Strain-specific differential PCR was performed for kgp and fimA using DNA isolated from subgingival plaque samples. Our findings demonstrate that all of the P. gingivalis kgp biotypes detected in this study were predominantly associated with the fimA II genotype. Dominance of kgp biotypes 381 or HG66 combined with fimA II fimbriae could imply an adaptive strategy by P . gingivalis to generate the fittest strains for survival in the host environment. A perspective on possible adaptive strategies by Porphyromonas gingivalis to generate the fittest strains for survival in the host environment. A perspective on possible adaptive strategies by Porphyromonas gingivalis to generate the fittest strains for survival in the host environment.